Dynamic analysis and optimization of SiC reinforced Al6082 and Al7075 MMCs. (13th February 2019) - Allien, Vipin J; Kumar, Hemantha; Desai, Vijay
Abstract: Composites play a vital role in engineering applications. The main aim of this study was to analyse how addition of SiC will improve the damping properties of metal matrix composites (MMCs). The strengthening of composites depends on physical, mechanical and dynamic factors. In the present study, Al6082 and Al7075 aluminum alloy reinforced with (0, 1, 2, 3, 4, 5, 7.5, 10, 15 and 20) different weight percentages of silicon carbide particles (SiCp ) MMCs have been fabricated through stir casting method. The microstructure, density, hardness, tensile strength, impact strength, natural frequencies and damping ratio of the MMCs were determined. The mechanical tests and free vibration analysis results revealed that the addition of SiCp reinforcement enhanced the strength and stiffness of the aluminum alloy MMCs. Multi-attribute decision making (MADM) techniques like analytic hierarchy process (AHP) and technique for order preference by similarity to ideal solution (TOPSIS) methods were applied for determining the best fabricated MMCs. Based on MADM techniques, 15% SiC/Al7075 composite was selected as the best material and using response surface methodology (RSM) 13.66% SiC/Al7075 composite was found as the optimal composite material.